Complexity of parental prenatal attachment during pregnancy at risk for preterm delivery. (3rd March 2016) - Pisoni, Camilla; Garofoli, Francesca; Tzialla, Chryssoula; Orcesi, Simona; Spinillo, Arsenio; Politi, Pierluigi; Balottin, Umberto; Tinelli, Carmine; Stronati, Mauro
Abstract: Objective : To clarify the links between parents' prenatal attachment and psychosocial perinatal factors such as maternal depression, anxiety and social support. Methods : Cross-sectional study including 43 couples with high-risk pregnancy (RP) and 37 with physiologic pregnancy (PP). Self-report measures (depression, anxiety, social support and prenatal attachment) are completed by mothers, prenatal attachment questionnaire by fathers. Results : Depression ( p  < 0.001) and state anxiety ( p  < 0.001) are higher in RP. Both, maternal and paternal antenatal attachment is significantly lower in RP ( p  < 0.001; p  < 0.005) but not related to depression or anxiety. Paternal antenatal attachment is strictly related to the maternal attachment scale in both groups (PP: r  < 0.034; RP: r  < 0.004) and paternal antenatal scores in RP have a negative significant correlation with mothers' depression ( r  < 0.095). Conclusion : Hospitalized expecting parents at risk of preterm delivery develop less attachment to the fetus and higher levels of anxiety and depression compared to the physiologic pregnancy group. Maternal antenatal attachment is an independent variable related to the diagnosis of a possible preterm delivery. The promotion of prenatal psychological well-being and attachment for future mothers and fathers may serve to improve maternal health practices, perinatal health and neonatal outcome.